2016 IEEE International Conference on Communications (ICC) 2016
DOI: 10.1109/icc.2016.7511629
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-band radiation measure for MIMO arrays with beamformed transmission

Abstract: The spatial characteristics of the out-of-band radiation that a multiuser MIMO system emits in the environment, due to its power amplifiers (modeled by a polynomial model) are nonlinear, is studied by deriving an analytical expression for the continuous-time cross-correlation of the transmit signals. At a random spatial point, the same power is received at any frequency on average with a MIMO base station as with a SISO base station when the two radiate the same amount of power. For a specific channel realizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…This demonstrates that by increasing the number of antennas at the BS, OOB emissions due to low-resolution DACs can be significantly reduced. Similar findings have been reported for PAs in [14].…”
Section: A Spectral and Spatial Emissionssupporting
confidence: 91%
“…This demonstrates that by increasing the number of antennas at the BS, OOB emissions due to low-resolution DACs can be significantly reduced. Similar findings have been reported for PAs in [14].…”
Section: A Spectral and Spatial Emissionssupporting
confidence: 91%
“…In other directions, however, barely any distortion is received from the array, which stands in contrast to the single-antenna array that radiates distortion in all directions. This point was not correctly described in [1], where it was claimed that the distortion always has an array gain smaller than the desired signal. Figure 6 shows how the maximum beamforming gain at the out-of-band frequency f = B is changing as the number of users increases.…”
Section: Remarkmentioning
confidence: 99%
“…Part of this work was presented at IEEE International Conference on Communications in 2016 [1]. paper is to give a rigorous description of the distortion created by nonlinear hardware in multi-antenna transmitters, and to quantify to which degree the distortion combines coherently.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the nonlinear distortion analysis in the previous section, we formulate the proposed DPD structure and learning philosophy in this section keeping in mind that the main objective is to primarily minimize the harmful emissions in the intended RX direction, i.e., the in-band and OOB nonlinear distortion products in the effective combined signal y(n) expressed in (5).…”
Section: A Proposed Dpd Structurementioning
confidence: 99%
“…These studies show that the spectral efficiency and the energy efficiency, both of which are fundamental objectives of massive MIMO, are compromised. In [5], the out-of-band radiation due to PA nonlinearity was analyzed in both single antenna and massive MIMO transmitter scenarios, assuming a memoryless polynomial model for each PA unit. It was shown that the adjacent channel leakage ratio (ACLR) due to PA nonlinearity in the massive MIMO scenario is, on average, equal to the single antenna scenario when transmitting with the same total sum-power.…”
Section: Introductionmentioning
confidence: 99%